1966
DOI: 10.1042/bj0980438
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sex and gonadal hormones on rat plasma lipids during the development of an essential fatty acid deficiency

Abstract: 1. Male, female and castrated rats treated with oestradiol (30mug./week) or testosterone (2mg./week) were given an essential fatty acid-deficient diet containing 10% of hydrogenated coconut oil for 9 weeks. The concentrations and fatty acid composition of plasma phospholipids, cholesteryl esters and triglycerides were determined. 2. Between the second and third weeks of the deficiency, concentrations of plasma cholesteryl esters, phospholipids and triglycerides decreased, then remained relatively constant. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
10
1

Year Published

1968
1968
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 39 publications
3
10
1
Order By: Relevance
“…While a specific mechanism for increased 20:3n-6 concentrations with oral estrogen use is unknown, it has been suggested that estrogen may increase the biosynthesis of AA from LA. 1,2,4 The results from the present studies do not show significant increases in AA in serum phospholipid, but there was a tendency (P = 0.064) in study B for increased AA levels in the women receiving HRT as compared with women not receiving HRT. The higher level of AA/LA seen in study B, which was also nonsignificantly higher in study A, provides some support for the possibility of increased AA synthesis with oral estrogen use.…”
Section: Stark Et Alcontrasting
confidence: 55%
See 1 more Smart Citation
“…While a specific mechanism for increased 20:3n-6 concentrations with oral estrogen use is unknown, it has been suggested that estrogen may increase the biosynthesis of AA from LA. 1,2,4 The results from the present studies do not show significant increases in AA in serum phospholipid, but there was a tendency (P = 0.064) in study B for increased AA levels in the women receiving HRT as compared with women not receiving HRT. The higher level of AA/LA seen in study B, which was also nonsignificantly higher in study A, provides some support for the possibility of increased AA synthesis with oral estrogen use.…”
Section: Stark Et Alcontrasting
confidence: 55%
“…I nfluences of hormone replacement therapy (HRT) on fatty acid compositions of various plasma and serum lipids have been investigated previously, [1][2][3][4][5] but most of this research failed to examine the n-3 polyunsaturated fatty acid (PUFA) levels in serum phospholipid. Levels of n-3 PUFA in serum phospholipid as a physiological biomarker are important as eicosapentaenoic acid (EPA, 20:5n-3), docosapentaenoic acid (DPA, 22:5n-3), and docosahexaenoic acid (DHA, 22:6n-3) have been inversely associated with myocardial infarction and coronary heart disease (CHD) risk.…”
mentioning
confidence: 99%
“…Female rats retain higher levels of 20:4n-6 (arachidonic acid, AA) in tissues during EFA deficiency (3,7). Female sex hormones may facilitate the conversion of 18:2n-6 (linoleic acid, LA) to AA (7,8).…”
mentioning
confidence: 98%
“…Male animals are generally more susceptible than female animals to essential fatty acid (EFA) deficiency (1)(2)(3)(4)(5)(6)(7)(8). Female rats retain higher levels of 20:4n-6 (arachidonic acid, AA) in tissues during EFA deficiency (3,7).…”
mentioning
confidence: 99%
“…2). However, a con sistently higher level of arachidonic acid, a precursor of PG's, has been found in female rats, not only in tissues such as liver and heart but also in the plasma (10,11). Moreover, it is generally considered that tissue levels of PG's are regulated by the availability of their precursors, and PG synthesis is initiated by the release of free precursors from phospholipids or triglycerides (12).…”
Section: Discussionmentioning
confidence: 99%